Temporal changes in attention to sad and happy faces distinguish currently and remitted depressed individuals from never depressed individuals. Issue 2 (15th December 2015) - Soltani, Sabine; Newman, Kristin; Quigley, Leanne; Fernandez, Amanda; Dobson, Keith; Sears, Christopher
Abstract: Depression is associated with attentional biases for emotional information that are proposed to reflect stable vulnerability factors for the development and recurrence of depression. A key question for researchers is whether those who have recovered from depression also exhibit attentional biases, and if so, how similar these biases are to those who are currently depressed. To address this question, the present study examined attention to emotional faces in remitted depressed ( N =26), currently depressed ( N =16), and never depressed ( N =33) individuals. Participants viewed sets of four face images (happy, sad, threatening, and neutral) while their eye movements were tracked throughout an 8-s presentation. Like currently depressed participants, remitted depressed participants attended to sad faces significantly more than never depressed participants and attended to happy faces significantly less. Analyzing temporal changes in attention revealed that currently and remitted depressed participants did not reduce their attention to sad faces over the 8-s presentation, unlike never depressed participants. In contrast, remitted depressed participants attended to happy faces similarly to never depressed participants, increasing their attention to happy faces over the 8-s presentation. The implications for cognitive theories of depression and depression vulnerability are discussed. Highlights: Eye gaze tracking used to measure attention to sad, happy, angry, and neutral faces. Remitted depressed, currently depressed, and never depressed groups compared. Remitted depressed participants exhibited biased attention to sad and happy faces. Results indicate that attentional biases can be observed outside of depressive episodes.